PENERAPAN KURIKULUM TINGKAT SATUAN PENIDDIKAN (KTSP) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MADRASAH ALIYAH - Mubarak, Ahmad Zaki (Pascasarjana UIN ANTASARI Banjarmasin, 2008)
Teachcrs are the key people for the success of KTSP curriculum implementation. This isbeiause teachers are the implanters of the curriculum